Pela Gandong as a Manifestation of Religious Moderation in Maluku Society: A Bibliometric Analysis - Haris, Rahmadani (Widyadewata, 2025)
Pela Gandong is a local tradition in Maluku that stands as strong symbol of religious moderation, uniting Muslim and Christian communities in brotherhood that transcends religious differences. This tradition has played key role in maintaining harmony and has become model for conflict resolution based on local wisdom. This study aims to analyze research trends on Pela Gandong in context of religious moderation. Using bibliometric methods, this research traces trends in studies, citations, and collaborative networks among researchers to gain deeper understanding of development of studies on Pela Gandong. The findings show that number of publications related to Pela Gandong has increased, but there are still gaps in research that systematically examine this tradition within the context of religious moderation. Most previous studies have focused on historical and anthropological aspects of culture, while religious moderation dimension has not been extensively explored. Pela Gandong demonstrates how local wisdom can serve as an effective model of religious moderation, fostering interfaith harmony through values of tolerance, cooperation, and mutual assistance. This article also finds that Pela Gandong not only functions as a post-conflict resolution mechanism in Maluku, but also has potential to be adapted in other regions of Indonesia facing similar challenges in interreligious relations. In conclusion, Pela Gandong offers a relevant and effective model of religious moderation, yet further research is needed to understand how this tradition can be sustained and adapted in context of modernization and current social challenges, including introducing its values to younger generations.